2011
DOI: 10.1523/jneurosci.4518-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the Human Neocortex to the Temporal Dynamics of Attended Events

Abstract: Previous studies raise the hypothesis that attentional bias in the phase of neocortical excitability fluctuations (oscillations) represents a fundamental mechanism for tuning the brain to the temporal dynamics of task-relevant event patterns. To evaluate this hypothesis, we recorded intracranial electrocortical activity in human epilepsy patients while they performed an audiovisual stream selection task. Consistent with our hypothesis, (1) attentional modulation of oscillatory entrainment operates in a distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

32
210
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(244 citation statements)
references
References 33 publications
32
210
0
Order By: Relevance
“…Auditory studies have similarly investigated the impact of pre-target oscillatory state but did so mostly in paradigms in which oscillations were driven by discrete and periodic stimuli. These auditory studies found effects mostly at lower frequencies, such as the delta and theta bands (Luo and Poeppel, 2007;Lakatos et al, 2009;Schroeder and Lakatos, 2009;Stefanics et al, 2010;Besle et al, 2011;Ding and Simon, 2012). Our results reiterate this importance of theta-band over alpha-band oscillations in auditory cortex for stimulus detection.…”
Section: Role Of Oscillatory State For Perceptionsupporting
confidence: 84%
See 1 more Smart Citation
“…Auditory studies have similarly investigated the impact of pre-target oscillatory state but did so mostly in paradigms in which oscillations were driven by discrete and periodic stimuli. These auditory studies found effects mostly at lower frequencies, such as the delta and theta bands (Luo and Poeppel, 2007;Lakatos et al, 2009;Schroeder and Lakatos, 2009;Stefanics et al, 2010;Besle et al, 2011;Ding and Simon, 2012). Our results reiterate this importance of theta-band over alpha-band oscillations in auditory cortex for stimulus detection.…”
Section: Role Of Oscillatory State For Perceptionsupporting
confidence: 84%
“…For example, psychophysical perceptual performance correlates with specific states of spontaneous prestimulus oscillations, as shown by correlations between alpha-band power and visual detection rates (Romei et al, 2008;van Dijk et al, 2008) and dependencies of detection rates on the phase of ongoing oscillations (Busch et al, 2009;Mathewson et al, 2009;Busch and VanRullen, 2010). Such effects of prestimulus oscillatory state on perception can be further enhanced by expectation or attention Schroeder and Lakatos, 2009;Stefanics et al, 2010;Besle et al, 2011) and also manifest in occulomotor responses . These findings promote speculations about a periodic processing mode of sensation Giraud and Poeppel, 2012;Jensen et al, 2012), whereby discrete windows of opportunity control the entry of stimuli to cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Recordings from macaque auditory cortex (3,9,10), human auditory cortex (11), and human electroencephalography (EEG) recordings (12)(13)(14) confirm that delta phase reorganizes in response to rhythmic auditory stimulation and that optimal phase aligns to expected times of event onsets. The results are amplified event-related potentials (ERPs) and increased firing in response to stimulus onsets (3,15).…”
mentioning
confidence: 87%
“…gamma range, N 40 Hz) provide a reliable index of feature binding within and across sensory modalities (Arnal et al, 2011;Engel et al, 1991;Roelfsema et al, 1997;Senkowski et al, 2008;Tallon-Baudry and Bertrand, 1999). In multisensory integration, low-frequency neural oscillations (delta, 1-2 Hz) play a crucial role in the temporal selection (Besle et al, 2011;Fiebelkorn et al, 2013;Gomez-Ramirez et al, 2011;Lakatos et al, 2008;Schroeder and Lakatos, 2009) and in the integration of AV information (Fiebelkorn et al, 2011;Kösem and van Wassenhove, 2012;Luo et al, 2010).…”
Section: Neural Oscillations: Multiplex Encoding Of Informationmentioning
confidence: 99%
“…Here, we hypothesize that the brain could use oscillatory entrainment to establish a temporal reference frame and we thus ask whether the phase of entrained neural oscillations actually encodes the "when" of perception. Specifically, the preferred phase of oscillatory entrainment is known to be context-dependent (Besle et al, 2011;Gomez-Ramirez et al, 2011;Lakatos et al, 2008;Rees et al, 1986), suggesting that neural entrainment may not be a passive neural response. Additionally, preferential phases of entrained neural oscillations are subject-specific (Besle et al, 2011), making this neural index particularly well-suited for investigating the highly subjective and variable nature of time perception.…”
Section: Introductionmentioning
confidence: 99%